POTENTIAL PRODUCTION OF THE FIVE PREDOMINANT SMALL PELAGIC FISH SPECIES GROUPS IN THE JAVA SEA - Purwanto Purwanto; Duto Nugroho; Suwarso Suwarso (Indonesian Fisheries Research Journal, 2014)
The Java Sea is one of the important fishing areas for small pelagic fishery in Indonesia. The production of the fishery was dominated by five fish species groups. To support the management of  that  fishery,  an  assessment  of  the  stock  of  the  five  predominant  small  pelagic  fish  species groups was conducted. Based on the result of analysis, the maximum sustainable yield (MSY) of the stock of five predominant small pelagic fish species was about 244.6 thousand tons. Meanwhile, the MSY of the stock of the whole exploitable small pelagic fish species was about 315.5 thousand tons. The optimum fishing effort (EMSY) was 1032 units. The total fishing effort was higher than EMSY and the fish stock was likely over-exploited since 2000. To ensure the optimal fish production of the small pelagic fish stock in the Java Sea, it is necessary to recover fish stock by controlling fishing effort to EMSY. The time which it takes for the fish stock to recover was about two years when fishing effort was reduced from its level in 2009 to EMSY.